2007
DOI: 10.1002/gps.1795
|View full text |Cite
|
Sign up to set email alerts
|

Chinese demented inpatients admitted following a suicide attempt: a case series

Abstract: These cases, taken together, suggest that suicide attempt can occur in patients with dementia. It is important for clinicians to be aware of the risk of suicide in patients with dementia, especially those associated with delusions, even if they have no major depression or suicide attempt history. Antidepressants and antipsychotics may play a critical role in the treatment of suicide attempt in dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…In addition, personality changes based on declining cognitive capacity and the neurochemical imbalances described in late‐life depression and in dementia might predispose patients to aggressive or impulsive acts, such as suicide attempts. Barak and Aizenberg found that suicide attempts occurred in 4.7% of all dementia cases; the rate of suicide attempts found in another case series was 11.7% of all dementia cases . Lim et al .…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…In addition, personality changes based on declining cognitive capacity and the neurochemical imbalances described in late‐life depression and in dementia might predispose patients to aggressive or impulsive acts, such as suicide attempts. Barak and Aizenberg found that suicide attempts occurred in 4.7% of all dementia cases; the rate of suicide attempts found in another case series was 11.7% of all dementia cases . Lim et al .…”
Section: Resultsmentioning
confidence: 93%
“…Tsai et al . propose delusions as a suicide risk factors in dementia: in their study seven demented patients attempted suicide . All their seven cases had delusions (e.g.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…8,[11][12][13][14] Although attempted suicides are reported to be rare among inpatients with dementia, 15,16 a recent Chinese study found that more than 10% of demented inpatients had been admitted after a suicide attempt. 17 The prevalence rate of suicidal ideation is estimated to range between 0.9% and 42%. 12,18 Specific types of dementia, such as Huntington and Alzheimer diseases, are mentioned by case reports as potential predictors for suicidal behavior.…”
mentioning
confidence: 99%